2019
DOI: 10.1016/j.jacbts.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Microvascular Endothelial Enhancement of Cardiomyocyte Function Is Impaired by Inflammation and Restored by Empagliflozin

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
137
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 151 publications
(155 citation statements)
references
References 59 publications
5
137
1
Order By: Relevance
“…demonstrated that Empagliflozin suppresses TNF-α-induced mitochondrial and cytoplasmic ROS accumulation, thereby restoring cardiac microvascular endothelial cell-derived NO delivery, which in turn leads to reinstatement of cardiac relaxation and contraction (79). There are great expectations regarding the result of these clinical trials because, at the time of writing, no drugs have been demonstrated to be effective for the treatment of HFpEF (80).…”
Section: Future Directionsmentioning
confidence: 99%
“…demonstrated that Empagliflozin suppresses TNF-α-induced mitochondrial and cytoplasmic ROS accumulation, thereby restoring cardiac microvascular endothelial cell-derived NO delivery, which in turn leads to reinstatement of cardiac relaxation and contraction (79). There are great expectations regarding the result of these clinical trials because, at the time of writing, no drugs have been demonstrated to be effective for the treatment of HFpEF (80).…”
Section: Future Directionsmentioning
confidence: 99%
“… 19 In addition, well-functioning mitochondria can buffer [Ca 2+ ]i by active absorption, whereas damaged mitochondria release calcium into the cytoplasm, causing [Ca 2+ ]i overload. 20 Although mitochondrial damage and [Ca 2+ ]i have been shown to promote cardiac microvascular I/R injury, 21 the underlying molecular mechanisms are not known.…”
Section: Introductionmentioning
confidence: 99%
“…Along the same line, the SGLT2i empagliflozin was recently found to modulate hyperglycemia-induced microvascular oxidative stress by modulating the p38 MAPK/miR-21 pathway (83). This finding is interesting as recent work has shown that improvement of microvascular function by SGLT2i reduces myocardial inflammation and oxidative stress (84), important features contributing to heart failure development in people with diabetes (85). Although these studies raise significant interest, more research is needed to appraise how new glucose-lowering drugs induce changes of miRNA landscape, and whether these changes are causally implicated in the disease development.…”
Section: Toward Personalized Epigenetic Therapiesmentioning
confidence: 83%